The Intervention of Music Therapy on Behavioral Training of High-Functioning Autistic Children under Intelligent Health Monitoring - Rugui He (Applied Bionics and Biomechanics)
Autism is a serious and widespread developmental disorder in children. With the increase of autistic children every year, it is necessary to study a set of effective music therapy activities that can penetrate into life to help autistic children’s rehabilitation training. This paper aims to study the behavioral training of high-functioning autistic children with music therapy intervention under intelligent health monitoring. The autistic children were selected and divided into experimental group and control group. According to the psychological and physiological characteristics of five autistic children aged 5-7 years in the experimental group, the music therapy activity plan was designed, and the experimental intervention was carried out by combining individual music therapy and group music therapy. Compared with the control group, this paper explores the effect of music on the treatment of children with autism. The experimental results of this paper show that the language, social, cognitive, and behavioral problems of autistic children under music therapy under intelligent health monitoring have been significantly improved, and their emotional response ability has improved the most, increasing by 34%. Communication ability was next, increased by 20.3%; motor coordination ability increased by 20%; and cognitive ability improved by 11%. It can be explained that the four aspects of language, social interaction, cognition, and behavior have been significantly improved after music therapy.